Blockchain-Enabled Supply Chain Finance: A Bibliometric Review and Research Agenda - Asaduddin Abdullah; Arif Satria; Heti Mulyati; Yandra Arkeman; Dikky Indrawan (Administrative Sciences)
The COVID-19 pandemic has revealed weaknesses in traditional supply chain finance systems, highlighting the need for digital change. Blockchain technology, with its ability to create secure and transparent records of transactions, offers a potential solution. This study uses bibliometric analysis and a literature review to examine research on blockchain-enabled supply chain finance, drawing on a database of 446 articles from ScienceDirect and Scopus. The findings show a growing interest in how blockchain can improve transparency, efficiency, and security in supply chain finance, addressing challenges like information asymmetry. This study suggests future research should focus on real-world applications of blockchain, how it can be used with other technologies, regulations and governance, and the social and environmental impacts of blockchain-based supply chain finance. This research also highlights the different priorities of the Global North and South in blockchain-enabled supply chain finance. The North focuses on efficiency and traceability, while the South emphasizes adding value and transparency. A lack of research on fair pricing, especially in the Global South, points to a critical gap that future research needs to address to ensure fairness in global trade.